Some thoughts about Francesca Albanese's expert lecture "Legal aspects of human rights violations and the Geneva Conventions in the occupied Palestinian territories" held in Maribor, Slovenia - Stajnko, Jan (Pécs journal of international and European law, 2025)
On 8 July 2025, the Department of Criminal Law, Faculty of Law at the University of Maribor, hosted Francesca Albanese, the international law expert and UN Special Rapporteur on the situation of human rights in the Palestinian territories occupied since 1967. In this contribution, the views shared at her expert lecture titled "Legal aspects of human rights violations and the Geneva Conventions in the occupied Palestinian territories" are outpined. Additionally, some concerns are raised regarding implications of Albanese's views for the EU criminal law, in particular the legislative framework aiming at harmonization of the so-called hate speech offences under the Framework Decision 2008/913/JHA.